Effects of Radiation Doses on the Photostimulated Luminescence Response of Certain Herbs and Spices - Sandeva, Ivana; Spasevska, Hristina; Ginovska, Margarita; Stojanovska-Georgievska, Lihnida (Walter de Gruyter GmbH, 2017)
Abstract Ionizing radiation applied on food eliminates harmful microorganisms, prevents sprouting and delays ripening. All methods for detection of irradiated food are based on physical, chemical, biological or microbiological changes caused by the treatment with ionizing radiation. When minerals are exposed to ionizing radiation, they accumulate radiation energy and store it in the crystal lattice, by which some electrons remain trapped in the lattice. When these minerals are exposed to optical stimulation, trapped electrons are released. The phenomenon, called optically stimulated luminescence or photostimulated luminescence, occurs when released electrons recombine with holes from luminescence centers in the lattice, resulting in emission of light with certain wavelengths. In this paper, the results of measurements performed on seven different samples of herbs and spices are presented. In order to make a comparison between luminescence signals from samples treated with different doses, unirradiated samples are treated with Co-60 with doses of 1 kGy, 5 kGy and 10 kGy. In all cases it was shown that the higher the applied dose, the higher the luminescence signal.